Effect of potassium‐waterglass composition on strength development and leaching behavior of geopolymers in different curing conditions - Umberto C. C. S. Siciliano; Ana C. C. Trindade; Flávio de Andrade Silva (International Journal of Ceramic Engineering & Science)
Abstract This study delves into the impact of different potassium‐waterglass (K‐WG) compositions on the early reaction dynamics and strength evolution in metakaolin‐based geopolymers (GP). By maintaining a constant SiO2/Al2O3 ratio of 4, the study explores the influence of varying H2O/K2O and K2O/Al2O3 ratios on GP properties under both dry and saturated curing conditions. Early reaction kinetics are examined using isothermal calorimetry at room temperature (21°C), and pH measurements provide insights into alkali leaching. A strong correlation was found between total heat release and strength gain, as evidenced by ultrasonic cement analyzer (UCA) readings. The study further identifies that increased H2O/K2O ratios prolong setting times and delay the geopolymerization peaks, while a higher K2O/Al2O3 ratio enhances the geopolymerization process. Vicat tests confirmed the results obtained by calorimetry and UCA: only the GP4 formulation (H2O/K2O = 8.7 and K2O/Al2O3 = 1.3) hardened in less than 7 days. Additionally, it was found that saturated curing conditions decelerate strength development, with an initial notable decline in compressive strength at 24 h compared with dry curing. However, this difference diminishes to a negligible 7.6% after 3 days. Optimal ratios of H2O/K2O = 8.7 and K2O/Al2O3 = 1.3 were determined to be critical for achieving reliable strength measurements at 1 day of curing. pH assessments indicated strong water resistance in all GP formulations, with leaching primarily governed by diffusion mechanisms. Specifically, the K‐WG composition with SiO2/K2O = 1.53 and H2O/K2O = 8.69 showcased minimal leachability. These fundamental findings are crucial for the later design of GP materials that require rapid strength development, especially crucial for applications necessitating cementing under extreme conditions, such as deep‐sea drilling, geothermal energy production, and high‐temperature industrial processes.